State Protection Against Action Of Persection And Intolerance During The Covid-19 Pandemic - Pawennei, Mulyati; Mery, Lisa; Arief, Syamsiar (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2021)
The purpose of writing this article is to focus on how the Indonesian state in accordance with the Contitution, makes the protection of citizen’ rights as one of the main characteristics of the implementation of human rights. In the process important issues that deserve to be studied in depth were discovered (1) the role of the state institutionally protecting citizens from acts of persecution and intolerance that also occurred during the Covid-19 pandemic; (2) prevention of acts of persecution and intoleranceaffecting the life of the nation and state in the past five years occurated in the Covid-19 pandemic. The results of the study provide a perspective that legal efforts which are a form of the existence of the practice of Pancasila and UUD 1945 including the implementation of protection of human rights in Law number 39/1999 concerning Human Rights as legal umbrella that must be upright and firm in its implementation, because law emforcement in human rights will fatale consequences with the destruction of diversity in the Republic of Indonesia, during the Covid-19 pandemic it turned out that persecution and intolerance continued and needed consistency in the protection of human rights law in accordance with the mandate of Pancasila as a value and UUD 1945 as a legal norm.